Pharmaceutical Pollution Alters the Structure of Freshwater Communities and Hinders Their Recovery from a Fish Predator - Michelangeli, Marcus; Martin, Jake M; Robson, Stephanie; Cerveny, Daniel; Walsh, Robert; Richmond, Erinn K; Grace, Michael R; Brand, Jack A; Bertram, Michael G; Ho, Susie S Y; Brodin, Tomas; Wong, Bob B M (Environmental science & technology, 2024)
Freshwater ecosystems are under threat from rising pharmaceutical pollution. While such pollutants are known to elicit biological effects on organisms, we have limited knowledge on how these effects might cascade through food-webs, disrupt ecological processes, and shape freshwater communities. In this study, we used a mesocosm experiment to explore how the community impacts of a top-order predator, the eastern mosquitofish (Gambusia holbrooki), are mediated by exposure to environmentally relevant low (measured concentration: ∼10 ng/L) and high concentrations (∼110 ng/L) of the pervasive pharmaceutical pollutant fluoxetine. We found no evidence that exposure to fluoxetine altered the consumptive effects of mosquitofish on zooplankton. However, once mosquitofish were removed from the mesocosms, zooplankton abundance recovered to a greater extent in control mesocosms compared to both low and high fluoxetine-exposed mesocosms. By the end of the experiment, this resulted in fundamental differences in community structure between the control and fluoxetine-treated mesocosms. Specifically, the control mesocosms were characterized by higher zooplankton abundances and lower algal biomass, whereas mesocosms exposed to either low or high concentrations of fluoxetine had lower zooplankton abundances and higher algal biomass. Our results suggest that fluoxetine, even at very low concentrations, can alter aquatic communities and hinder their recovery from disturbances.
Keywords: invasive species; primary productivity; Zooplankton; pharmaceuticals; Cyprinodontiformes; chemical contaminants; ryby; Food Chain; Ecosystem; fluoxetine; zvířata; sladká voda; Fishes; Fresh Water; zooplankton; Water Pollutants, Chemical; Animals; fluoxetin; Fluoxetine; potravní řetězec; chemické látky znečišťující vodu; ekosystém